A comparative Study of Predicating the Essence and the Flimsy from the Viewpoint of Mulla Sadra and Ibn Arabi - Ramin Golmakani; Hadi Izanlou; Rasoul Padashpour (آموزه‌‌های فلسفه اسلامي, 2021)
Predicating the Essence and the Flimsy is one of Mulla Sadra's important innovations. The implication of this theory is that imperfect existence in perfect existence is more fully realized, so that the higher order encompasses all the lower perfections. Mulla Sadra achieved this theory by using the material of earlier philosophers and being influenced by Ibn Arabi. He explained this theory with his own principles such as the principality of existence, graded unity of being, the principle of unity-in-plurality, the simple rule of truth and causality. In this article, we have tried to examine the background and foundations of this theory along with Ibn Arabi's theories.